Characteristics of Inguinal Hernia Patients at Massenrempulu Hospital for the Period of 2023 - S, Fatma Dilla; Gani, Azis Beru; Zulfahmidah, Zulfahmidah; Purnamasari, Reeny; Mubarak, Andi Firman (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Hernia is a condition that can occur at all ages, characterized by a lump that appears and disappears. Inguinal hernia is the most common type, with lateral inguinal hernia accounting for 50%, medial 25%, and femoral 15%. About 15% of adults suffer from inguinal hernia, with prevalence increasing from 5–8% at ages 25–40 years to 45% at age 75. Hernia repair remains the most effective general surgical procedure. Objective: To determine the characteristics of inguinal hernia patients at Massenrempulu Hospital in 2023 based on age, occupation, classification, and body mass index (BMI). Methods: This study used a descriptive method with an observational design. Data were analyzed by frequency distribution according to research variables. Results: Inguinal hernia was more common in patients aged >66 years (45.9%), in heavy work occupations (70.3%), and classified predominantly as indirect/lateral inguinal hernia (94.6%). Based on BMI, most patients were in the overweight category (54.1%). Conclusion: At Massenrempulu Hospital in 2023, inguinal hernia was mostly found in patients aged >66 years, engaged in heavy work, with indirect/lateral classification, and overweight BMI